RANKL, OPG, and CTS‐K Release in Bone Response to Immediate Nonfunctional Loading of a Single Implant in Mandibular Molar Sites During Osseointegration Establishment - Xiaowen Hu; Yijie Fan; Xuexia Chen (Clinical and Experimental Dental Research)
ABSTRACT Objectives To verify that osseointegration maturation under immediate restoration is correlative with active release of cytokines. Material and Methods The participants needing the restoration of a single missing mandibular molar were randomized into immediate restoration (IR) and conventional restoration group (CR). All eligible patients were recalled for collecting peri‐implant crevicular fluid (PICF) samples according to the scheduled follow‐up time point during osseointegration and functional loading. Detection of receptor activator of nuclear factor‐KB ligand, osteoprotegerin, and cathepsin K in PICF was conducted to statistically analyze their difference between IR and CR groups. Results During the osseointegration period, the overall level of these cytokines in the IR group was statistically higher than that of the corresponding cytokine in the CR group. During functional loading, the overall level of the each cytokine in CR was statistically different from that of the corresponding cytokine during osseointegration, but the overall level of each cytokine was not statistically different between the two groups. Conclusions The rapid osseointegration maturation under immediate restoration is probably correlative with active release of cytokines related with bone metabolism.